2020
DOI: 10.1186/s12885-020-07399-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognostic signatures in triple-negative breast cancer based on the differential expression analysis via NanoString nCounter immune panel

Abstract: Background Triple-Negative Breast Cancer (TNBC) is an aggressive and complex subtype of breast cancer. The current biomarkers used in the context of breast cancer treatment are highly dependent on the targeting of oestrogen receptor, progesterone receptor, or HER2, resulting in treatment failure and disease recurrence and creating clinical challenges. Thus, there is still a crucial need for the improvement of TNBC treatment; the discovery of effective biomarkers that can be easily translated to the clinics is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Indeed, Matrilysin is a validated target of several compounds that could be proposed to personalise BL1 TNBC. At the same time, PGBD5 levels were found significantly higher in basal-like BC [ 24 ], and the same goes for CALML5, one of the top expressed genes in TNBC samples [ 25 ], PADI2 [ 26 ] and KLRG2 [ 27 ]. Gong et al demonstrated that the upregulation of MGP promotes the proliferation of cancer which probably makes it a novel biomarker or therapeutic target for TNBC patients [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, Matrilysin is a validated target of several compounds that could be proposed to personalise BL1 TNBC. At the same time, PGBD5 levels were found significantly higher in basal-like BC [ 24 ], and the same goes for CALML5, one of the top expressed genes in TNBC samples [ 25 ], PADI2 [ 26 ] and KLRG2 [ 27 ]. Gong et al demonstrated that the upregulation of MGP promotes the proliferation of cancer which probably makes it a novel biomarker or therapeutic target for TNBC patients [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
“…This panel is therefore ideal for studying immune-related conditions and diseases. A key advantage of this NanoString technology is the ability to directly quantify molecules of interest in the absence of an amplification step, which prevents introduction of artificial bias [ 25 ]. Gene expression data were pre-processed and normalized using author-defined methods.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters s jk are assumed to have a probe specific mean t j and a shared variance τ 2 , as the points by probe in Figure 2(d) have centers clearly distinct from one another but have similar variability. We further enforce the constraints shown in (10), to avoid issues with identifiability, making s jk dependent on other probe effects from the same dataset. We include these constraints to stabilize our distribution in the absence of strong prior information, relying on the fact that the log-transformed positive probe data have a strong linear relationship with the log-transformed control RNA expression levels in each study alone.…”
Section: Designmentioning
confidence: 99%
“…This has led to a ubiquity of FFPE samples and has made the nCounter system an invaluable resource in medical research. Among other areas, the nCounter framework has been used to analyze FFPE samples in studies of colon, breast, and lung cancer [5, 10, 17]. However, a significant downside to using FFPE samples is the level of mRNA “modification” during the preservation and storage of the sample [11], causing higher levels of variability and uncertainty in the readings.…”
Section: Introductionmentioning
confidence: 99%